The efficacy and safety of cuttlebone for lowering serum phosphate in patients with end-stage renal disease: a meta-analysis of randomized controlled trials - Chen, Hsiao-Tien; Hung, Kuo-Chuan; Hsu, Chin-Wei; Chen, Jui-Yi; Liu, Chien-Cheng; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Pharmacology, 2023)
Background: The efficacy of cuttlebone for treating hyperphosphatemia in patients with end-stage renal disease and its safety remained unclear. Methods: Randomized controlled trials comparing the efficacy of cuttlebone with conventional interventions were retrieved from MEDLINE, EMBASE, Cochrane Library, Airiti Library, and other major Chinese databases until 1 February 2023. The primary outcome was circulating phosphate concentration, while secondary outcomes included circulating calcium and intact parathyroid hormone levels, calcium–phosphorus product, and treatment-related side-effects. Results: Analysis of nine studies published between 2000 and 2019 including 726 participants showed a lower circulating phosphate concentration in the cuttlebone group than in controls [mean difference (MD) = −0.23, 95% CI: −0.39 to −0.06, p = 0.006, I2 = 94%, 726 patients] and a dose-dependent effect of cuttlebone against hyperphosphatemia. Therapeutic benefits were noted after both short-term (1–2 months) and long-term (3–6 months) treatments. Besides, patients receiving hemodialysis showed a better response to cuttlebone than those receiving peritoneal dialysis. There was no difference in circulating calcium level (mean difference = 0.03, 95% CI: −0.01 to 0.07, p = 0.17, I2 = 34%, 654 patients), while patients receiving cuttlebone showed lower circulating iPTH level and calcium-phosphorus product (MD = −43.63, 95% CI: −74.1 to −13.16, p = 0.005, I2 = 76%, 654 patients), (MD = −0.38, 95% CI: −0.38 to −0.01, p = 0.04, I2 = 83%, 520 patients). No difference in the risks of constipation, gastrointestinal discomfort, and elevated blood calcium was noted between the two groups. Conclusion: Compared with conventional phosphate-binding agents, cuttlebone more efficiently suppressed hyperphosphatemia with a dose-dependent effect. The limited number of included studies warrants further clinical investigations to verify our findings. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42023396300.